Optimizing Adaptive Agricultural Systems, Making Organic Fertilizer, and Drip Irrigation Technology in Sukamanah Village - Maulana, Adrian Rizki; Damayanti, Fujia; Nurlaela, Intan; Kusnayadi, Kusnayadi; Noval, Muhammad; Rifal, Rafi Muhammad; Alam, Rafi Sandina; Sulistiyo, Satria Putra; Jenab, Siti; Septiana, Fajar Indra (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This research aims to evaluate the effectiveness of several proposed solutions to improve the agricultural system. The main focus of this study is on introducing an adaptive agricultural system tailored to local environmental conditions, producing organic fertilizers using modern agricultural standards, and implementing drip irrigation technology. The results show that the introduction of an adaptive agricultural system significantly increases productivity through the selection of superior seeds and proper planting patterns. Furthermore, the production of organic fertilizer has proven to improve soil quality and crop yields through the layering method and the use of Effective Microorganisms (EM4). The application of drip irrigation technology enhances water use efficiency, reducing the overuse of water resources. Overall, these three solutions positively contribute to increased productivity, sustainability, and resource efficiency in modern agricultural systems.